(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
This article presents a comparative analysis of the physiological development of biotechnological potato genotypes (S-46, S-73, S-55, and S-17) under both in vitro and in vivo conditions. The research was conducted in the saline and arid climatic environment of the Bukhara region. The findings revealed that plant growth, chlorophyll concentration, biomass accumulation, and root system development were significantly enhanced in vivo. Notably, the S-17 genotype exhibited remarkable adaptability to saline and arid conditions. This study establishes a crucial scientific foundation for future investigations focused on the selection of potato varieties capable of thriving under drought and salinity stress.